Farmer performance in beef cattle production Intibona Village, Indonesia. Issue 1 (April 2020) - Amrawaty, A A; Hastang; Sumarni
Abstract: This study aims to understand the performance of breeders in beef cattle farming in the Tibona Village, Bulukumpa District, Bulukumba Regency. This research was conducted between May and July 2019. The samples for this study was drawn based on purposive sampling method. This research located in the most populated beef cattle in Bulukumba Regency which has the largest number of beef cattle populations, 2252. The population in this study were beef cattle breeders in Tibona Village, Bulukumpa district, Bulukumba Regency as many as 350 populations. There are seven hamlets in Tibona Village, each of which has two farmers/livestock groups while each group consist of 25 farmers. The research used descriptive analysis. The results of this study regarding the Performance of Farmers in Beef Cattle business in Tibona Village, Bulukumpa sub-district, District of Bulukumba, showed that overall, the performance of breeders in Tibona Village included in the category of good performance.